ROLE AND METHODS OF TECHNOLOGICAL FORECASTING IN ECONOMICS MODERNIZATION - N. N. Zelenov (Модернизация, инновация, развитие)
Technological forecasting is a process of prediction future technological characteristics, their distribution in time and the rate at whichtechnological parameters, attributes and capabilities change. An attempt is made in the paper to scrutinize the nature, history and practical application of technological forecasting, main methods and techniques currently used for these purposes, feasibility limits of each method, factors determining the choice of the most suitable method. Assessment is given to technological forecasting development prospects.